Pengaruh Penerapan SAK EMKM, Sistem Informasi Akuntansi, dan Ukuran Usaha Terhadap Kualitas Laporan Keuangan - Andari, Atik Tri; Asmoro, Wiwiek Kusumaning; Setianingsih, Novie Astuti; Fitriani, Dwi Rahma (Universitas Gorontalo, 2025)
This study aims to analyze the influence of the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), accounting information systems, and business size on the quality of financial statements. The subjects of this study are MSMEs engaged in the tofu processing industry located in the city of Kediri. This research uses multiple linear regression analysis. The results show that the implementation of SAK EMKM has a significant influence on the quality of financial statements. In addition, accounting information systems also have an effect on financial statement quality. Likewise, business size is proven to influence the quality of financial statements. Simultaneously, accounting information systems and business size collectively affect the quality of financial statements.